Bat functional traits associated with environmental, landscape, and conservation variables in Neotropical dry forests - Díaz-B, Camila A.; Otálora-Ardila, Aída; Valdés-Cardona, María Camila; López-Arévalo, Hugo F.; Montenegro, Olga L. (Frontiers in Forests and Global Change, 2023)
Tropical dry forests are among the most threatened ecosystems worldwide. Bats' role in those ecosystems is critical because of multiple bat-mediated processes. Such processes are strongly related to bats' functional traits. However, it is poorly known which bat's functional traits could relate to variations in environmental conditions in tropical dry forests. In this study, we tested the hypotheses that bat functional traits would be significantly associated with landscape variables, climatic variables, and land-use intensity. For testing these hypotheses, we used data from phyllostomid and mormoopid bats captured in mist nets and data from non-phyllostomid insectivorous bat species registered by passive acoustic monitoring. We considered six functional traits for phyllostomid and mormoopid bats, and for non-phyllostomid insectivorous bats, we added two echolocation parameters. We measured five environmental variables, two of local climate (daily maximum temperature and wind speed) and five of landscape features (total area of water and closeness, probability of finding caves, and conservation status). The relationships between bat functional traits and environmental variables were evaluated using the RLQ and the fourth corner analysis. We captured 360 individuals belonging to 14 species with mist nets (Phyllostomidae and Mormoopidae), and we identified 18 species and six sonotypes with acoustic sampling (Emballonuridae, Mormoopidae, Molossidae, Natalidae, Noctilionidae, and Vespertilionidae). We found that bats' functional traits related to environmental conditions were pulse structure, diet, vertical foraging stratification, and trophic level, although these relationships varied among bats' ecological roles. The hematophagous were related to water bodies' closeness, and animalivorous bats, mostly mormoopids, showed a relationship with the probability of finding caves. Insectivores bats that mostly forage on the canopy and emit qCF calls were significantly related to more conserved sites, and bats that emit qCF pulses were significantly associated with less area covered by water. Our findings provide insights into how bat functional traits vary in their relationships with environmental conditions in harsh environments such as dry forests.